Kajian Spasial Perubahan Luas dan Kerapatan Mangrove terhadap Abrasi di Desa Pejarakan, Buleleng - Whidayanti, Ella; Handayani, Tuty (PT. Pubsains Nur Cendekia, 2025)
The coastal village of Pejarakan, adjacent to West Bali National Park, has a fairly extensive mangrove ecosystem. Mangrove ecosystems have an important role as a protector of the coastline due to abrasion and accretion. Alterations in mangrove ecosystems along the coast of Pejarakan Village, caused by oceanographic factors and land-use changes, lead to changes in the coastline. This study aims to determine the relationship between changes in mangrove area and density to abrasion in Pejarakan Village within five years. The data needed in this study are remote sensing data of Landsat 8 OLI/TIRS satellite imagery in 2015 and 2020, analyzed using NDVI and single-band threshold methods. The results of this study show that the mangrove area along the coastline of Pejarakan Village has changed in mangrove coverage of 25.77 hectares, with an increasing level of density. These changes affect the occurrence of abrasion and accretion which results in changes in the coastline along the coastal coast of Pejarakan Village.